Ecological biomechanics of damage to macroalgae - Burnett, Nicholas P.; Koehl, M. A. R. (Frontiers in Plant Science, 2022)
Macroalgae provide food and habitat to a diversity of organisms in marine systems, so structural damage and breakage of thallus tissue can have important ecological consequences for the composition and dynamics of marine communities. Common sources of macroalgal damage include breakage by hydrodynamic forces imposed by ambient water currents and waves, tissue consumption by herbivores, and injuries due to epibionts. Many macroalgal species have biomechanical designs that minimize damage by these sources, such as flexibly reconfiguring into streamlined shapes in flow, having either strong or extensible tissues that are tough, and having chemical and morphological defenses against herbivores and epibionts. If damage occurs, some macroalgae have tissue properties that prevent cracks from propagating or that facilitate tissue breakage in certain places, allowing the remainder of the thallus to survive. In contrast to these mechanisms of damage control, some macroalgae use breakage to aid dispersal, while others simply complete their reproduction prior to seasonally-predictable periods of damage (e.g., storm season). Once damage occurs, macroalgae have a variety of biomechanical responses, including increasing tissue strength, thickening support structures, or altering thallus shape. Thus, macroalgae have myriad biomechanical strategies for preventing, controlling, and responding to structural damage that can occur throughout their lives.